Opinion Paper: Ethical Problems in Health Information Systems - Fessler, J.-M.; Grémy, F. (Methods of Information in Medicine, 2001)
Objectives: To introduce term and concept of infoethics and to argue on its importance for health information systems.Methods: To argue about our viewpoint of the dominance of the human component, which has been discussed at an IMIA working conference held in Helsinki, Finland (February 1998) devoted to the evaluation of health information systems.Results and conclusions: Any technology sets a relationship between human beings and their environment, both physical and human. No technology can be seen as merely instrumental. This is especially relevant when dealing with large automatic information systems, developed to contribute to the management and integration of large organizations, such as hospitals. In such a context, the environment is mainly made up of humans. In evaluating such information systems, human factors preside over merely technical factors. Even if satisfying the latter is mandatory, they are never really sufficient. A perfect hard- and software system can be an absolute failure in everyday use. In any information system, the human factor is, of course, human-computer interaction, which always occurs when one person interacts with the machinery. However, in a simultaneous multi-user context, human-human interaction is the main question to tackle. The evaluation of large information systems, such as those found in hospitals, is founded in the whole concept of inter-human relationships which underlie the design and use of the system. Indeed, such an information system predominately appears as a social system, with its psychological, sociological and ethical features.
Keywords: Health Information Systems; Hospital Information Systems; Ethics